Reducing the potential for injury in the home. How can Ergonomics help? - Hilary McDermott; Roger Haslam; Alistair Gibb (2007)
Within the UK we are experiencing a massive housing development programme with a commitment from government to increase the number of completed dwellings by 25% annually. Improving the design quality of new housing is a national priority and the research reported here aimed to verify how dwelling design interacts with human behaviour and how alternative design of new dwellings may reduce the potential for accidental injury within the home. Unsolicited questionnaires were delivered to a large number of new properties across the UK. Occupiers reported a number of problems with design features which had led to dissatisfaction and in some cases occupier modification. These findings support and validate previous work and reinforce how ergonomics principles in dwelling design may complement other strategies to improve occupier wellbeing and satisfaction.